Enhancing financial sustainability: the power of intellectual capital in India’s renewable energy industry - Faizi Weqar; Syed Noorul Shajar; Mohammad Kashif; Saqib Noman; Mohsin Khan (Humanities & Social Sciences Communications)
Abstract The main objective of this research article is to examine the effect of intellectual capital (IC) and its dimensions on the financial performance (FP) of the Indian renewable energy industry, guided by the Resource-Based View (RBV). The study employed data from 36 solar and 39 wind sector companies for six years, from 2017 to 2022. Moreover, the modified value added intellectual coefficient (MVAIC) model was used to measure the company’s IC. Further, the paper uses panel data regression analysis to examine the above-mentioned objectives. The results showed that IC improves the earnings and profitability of solar sector companies, while for wind sector companies, it only helps boost their profitability. Contrary to the expectation, human capital efficiency (HCE) failed to show any effect on the FP of the Indian solar sector companies. However, HCE positively moderates the relationship between structural capital efficiency (SCE) and FP, as well as relational capital efficiency (RCE) and FP. For the wind sector companies, HCE significantly and positively affects the FP; however, HCE negatively moderates SCE and profitability while positively for capital employed efficiency (CEE) and FP. This research adds new data from an industry that has previously received little attention (i.e. Indian renewable energy industry), thus broadening the research on the relationship between IC and FP. Moreover, the study may provide in-depth insights into the MVAIC dimensions as it discovers the moderating effect of human capital in boosting the company’s FP.